Anticonvulsant Profile of the Enantiomers of DL- HEPP-In-vitro and In-vivo Study - Ambriz-Hernandez, Ana L.; Cervantes-Espinoza, José G.; Vargas-Fernández, Eugenia; Cruz-Marín, Amelia de la; Buendía-Pazarán, José G.; Esquivel-Vargas, Javier; Góngora-Úbeda, Alexis G.; Peralta-Cruz, Javier; Chamorro-Cevallos, Germán; Meza-Toledo, Sergio E. (Pharmaceutical Science: New Insights and Developments Vol. 2, 2025)
Aims: Epilepsy is a brain disorder that is characterized by recurrent seizures. It affects 1% of the global population and remains poorly managed in 30% of patients despite available antiepileptic drugs, which often cause significant side effects even in controlled cases, highlighting the urgent need for improved treatments. In this paper, the resolution of DL-HEPP and the anticonvulsant activity and neurotoxicity of its enantiomers, as candidates for the treatment of refractory epilepsy, were reported. Study Design: Synthesis of DL-HEPP, separation of enantiomers (+)-HEPP and (-)-HEPP, and anticonvulsant profile and neurotoxicity of DL-HEPP and its enantiomers. Place and Duration of Study: This study was done at the Biochemistry, Pharmacy and Organic Chemistry Departments, Escuela Nacional de Ciencias Biológicas del Instituto Politécnico Nacional, Mexico City. The duration of the study is from 2012 to 2017. Methodology: In order to investigate differences in biological activity between HEPP enantiomers, the racemate was resolved using (-) brucine and (+) phenylethylamine salts of the acids. The optically active acids were esterified with diazomethane and reacted with ammonia to yield (+)-HEPP and (-)-HEPP. Enantiomeric purity was confirmed (>99% ee) using proton magnetic resonance with Europium tris-[3-(trifluoromethylhydroxymethylene)-(+)camphorate] and chiral HPLC. The anticonvulsant activity of DL-HEPP and its enantiomers was tested in pentylenetetrazole (PTZ), \(β\)-mercaptopropionic acid (\(β\)-MPA), bicuculline (BIC), thiosemicarbazide (TSC), and maximal electroshock (MES) seizure models. The rotarod ataxia test was used to evaluate neurotoxicity. Time-to-peak drug effects were established prior to dose-response studies. The duration of the anticonvulsant activity (+) and (-) HEPP was evaluated. Results: Chiral HPLC confirmed enantiomeric purity (>99% ee) for HEPP enantiomers. 1H and 13C-NMR spectra revealed identical chemical shifts for DL-HEPP and its enantiomers, the addition of Eu[TFH-cam-d] highlighted the stereochemical differences. DL-HEPP and its enantiomers exhibited a similar significant anticonvulsant activity in several acute seizure models in mice in nontoxic doses. Compounds DL-HEPP, (+) HEPP y (-) HEPP showed protective indexes (PI: 3.85, 3.66 and 4.14 respectively) outperforming sodium valproate (PI= 3.16) in the PTZ test. Neurotoxicity was comparable among DL-HEPP enantiomers. Over time, (-) HEPP maintained the highest protection, while the anticonvulsant activity of (+) HEPP declined rapidly against PTZ-induced seizures. Conclusion: At the time of peak drug effect (30 min), there are no differences either in the anticonvulsant activity against PTZ, BIC, TSC and b-MPA-induced seizures or in neurotoxicity between DL-HEPP and its enantiomers, which suggests that the optical resolution of DL-HEPP is not necessary for further preclinical studies. The protection of DL-HEPP and its enantiomers against convulsant drugs that block GABA neurotransmission suggests that they act in the GABAergic system. The research with enantiomers of HEPP provides valuable insights for the development of more effective and safer antiepileptic therapies.